Atitudes de profissionais de saúde frente à sexualidade, vulnerabilidade e prevenção as IST/HIV/AIDS em pessoas com transtornos mentais - Azevedo, Maria Renata Florencio de (2018)
The reorientation of the Mental Health care model in Brazil, from the hospital to the community, made possible the integration of the Mental Health Policy with the other Prevention and Care Policies of the Unified Health System, such as the Prevention of Sexually Transmitted Infections Policy (STIs / AIDS), making it possible to think about the vulnerability, improvement and prevention of aggravations in the sexual health of the population with mental disorders. Among the obstacles to the improvement of sexual health in the field of mental health are the difficulties of professionals to deal with the subject, and can be explained, mainly, by stigma and prejudice, of being perceived with uncontrolled sexuality or asexuality. Implies actions and reactions of denial and repression against the sexual experience in many health services. Therefore, understanding how the attitudes of health professionals are formed on this subject, it becomes urgent in the issues that involve the performance of professionals in the reduction, reproduction or increase of the vulnerability to STI/AIDS. To do so, based on the Theory of Rational Action and the Model of Vulnerability, this dissertation is composed of two studies. For this, based on the Theory of Rational Action and the Vulnerability Model, this dissertation is composed of two studies. Study 1: aimed on identifying how professionals perceive the sexuality of people with mental disorders. This was a qualitative cross-sectional study with an exploratory and descriptive character, carried out in Psychosocial Care Centers, located in the cities of João Pessoa, Campina Grande, Patos and Guarabira. The sample consisted of 27 female professionals, being 13 nurses, 11 psychologists and 3 social workers, located in the age group of 30 to 49 years, mostly. Regarding the time of operation, the majority varies from 1 to 5 years of service. Data were collected using a sociodemographic and occupational questionnaire and a semi-structured interview. The quantitative data were tabulated in the SPSS Software and analyzed by descriptive statistics and association, whereas for the qualitative results the thematic categorization was used. The results of these studies showed that, although most of the participants present positive attitudes towards sexuality, when it comes to the sexuality of users, negative attitudes are expressed through control, vigilance and silencing around the subject, being imperative the association of sexuality with the psychiatric condition, invalidating the possibilities of these users to experience sexuality. Also highlighted are aspects that make it difficult to manage sexuality within services: personal difficulties, lack of training, overload and lack of material resources. Study 2: aimed at analyzing the perception of the professionals about the vulnerability of psychiatric patients to STI / AIDS; and verify the prevention strategies developed or not in the mental health devices studied. This was a qualitative cross-sectional study with an exploratory and descriptive character, carried out in the same place and with the same sample from the first study. Data were collected using a sociodemographic and occupational questionnaire and a semistructured interview. The quantitative data were tabulated in SPSS Software and analyzed by descriptive statistics and association, whereas for the qualitative results, analysis of thematic categorization. The data have shown that when it comes to the perception of vulnerability to STI / AIDS, participants identify a worrying picture of vulnerability. However, the interventions expended, besides not integrating the promotion, prevention and care, are restricted to the individual and his psychiatric condition. At this juncture, the way in which prevention work is operationalized translates into assistance to cases understood as a risk to the health of users, those arriving as a demand to be solved by the service, resulting in the lack of assistance to those who are not identified as involved in cases of direct exposure.